Legal and Ethical Analysis of Mystery Box Transactions in E-Commerce Platforms: A Sharia Economic Law Perspective - Iwan Setiawan; Dudang Gojali; Chaerul Shaleh; Mualimin Mochammad Sahid (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
The phenomenon of mystery box trading on e-commerce platforms, such as Shopee, presents a paradox in the digital economy. On the one hand, it offers a thrill and appeal to consumers through an element of uncertainty. Still, on the other hand, it raises serious issues regarding the legal validity and ethics of transactions. The ambiguity of the object, the potential for loss, and exploitation through the mechanism of uncertainty require critical study within the realm of Islamic economic law. This study aims to analyze the conformity of mystery box trading practices with Islamic legal and ethical principles. This study uses a normative juridical method with a conceptual and normative-interpretive approach, grounded in the principles of Islamic jurisprudence (fiqh muamalah). Data were obtained through literature and documentation studies. The results show that mystery box transactions do not meet the requirements for a valid salam contract because the object of the goods is not described in detail, thus containing the prohibited gharar katsîr. From an ethical perspective, this practice contradicts the principles of justice, transparency, and consumer protection in Islamic transactions. The conclusion of this study is that mystery box trading is inconsistent with the legal and ethical principles of Islamic economics. Moreover, it is inappropriate for practice in Sharia-based transactions. And, this practice should be avoided to protect consumers and maintain the integrity of the Islamic digital market.